Clinical profiles of pediatric patients with GPP alone and with different IL36RN genotypes. Issue 3 (March 2017) - Wang, Yirong; Cheng, Ruhong; Lu, Zhiyong; Guo, Yifeng; Yan, Ming; Liang, Jianying; Huang, Peichen; Li, Ming; Yao, Zhirong
Highlights: There are minor clinical features implying different genotypes for childhood GPP alone patients. Epigenetic changes of IL36RN gene may play a role in those without mutation. Genetic diagnosis may provide prognosis for pediatric GPP alone patients. Most childhood GPP with both genotypes respond well to low-dose acitretin treatment. Abstract: Background: IL36RN mutation has been identified as one pathogenesis of generalized pustular psoriasis, but the existence of GPP patients without mutation makes this controversial. Objective: Our study aimed at assessing the differences in clinical profiles of children with GPP, with and without IL36RN mutation. Methods: An ambispective case series study involved review of the records of 66 childhood patients with pediatric-onset GPP and without previous psoriasis vulgaris. Results: c.115 + 6T > C was the most common mutation in this Chinese population with GPP alone. The age at onset was nearly halved in the homozygotes/compound heterozygotes than in IL36RN-negative patients. Besides a more severe inflammatory progression, three minor signs could prioritize patients with GPP for IL36RN screening (confluent lakes of pus (P = 0.002), perianal erosion (P = 0.014), and flexural erosion (P = 0.007)). More patients with the pathogenic mutation converted to ACH than those without mutation (χ2 = 4.773, P = 0.029). Children with GPP with or without IL36RN mutation responded well to oral low-dose acitretin, but IL36RN-positive cases suffered a much higher half-year recurrence rate after withdrawl of acitretin treatment(χ2 = 10.370, P = 0.001). Conclusions: Specific clinical features can remind dermatologists of the necessity of sequencing diagnosis. The mild pustular phenotype of those without mutation may imply the possible role of the epigenetic changes of IL36RN, or other IL36-blockers in the pathogenesis. Pediatric patients with GPP alone, both with and without IL36RN mutation responded well to low-dose acitretin.